2020
DOI: 10.21203/rs.3.rs-104354/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Impact of COVID-19 quarantine on dietary habits and physical activity in Saudi Arabia: a cross-sectional study

Abstract: Background: The COVID-19 pandemic has forced governments around the world to impose strict hygiene and national lockdown measures, which in turn has changed the dietary and lifestyle habits of the world’s population. Thus, the aim of this study is to evaluate whether dietary and physical activity behaviors of Saudi Arabia’s adult population changed during the COVID-19 quarantine.Methods: An electronic questionnaire was distributed on social media between June and July 2020 and was completed by 2,255 participan… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 40 publications
1
9
0
Order By: Relevance
“…As per this present study, results showed participant's daily consumption of milk or its product was increased [38.6% vs. 60%, P < 0.001)] whereas a study conducted by [8] reveals about 26% of study participants increased intake of milk or its products during Covid-19.…”
Section: Discussionsupporting
confidence: 51%
“…As per this present study, results showed participant's daily consumption of milk or its product was increased [38.6% vs. 60%, P < 0.001)] whereas a study conducted by [8] reveals about 26% of study participants increased intake of milk or its products during Covid-19.…”
Section: Discussionsupporting
confidence: 51%
“…The effect of COVID-19 lockdown on lifestyle has been thoroughly investigated. In Saudi Arabia, several authors observed significant reduction in physical activity and compliance with health diet in different subpopulations, which was associated with significant weight gain, along with deterioration in sleep quality [37] , [38] , [39] , [40] , [41] , [42] . Where such changes may have negative impact on healthy individuals, patients with preexisting comorbidities are exposed to greater health risks and quality of life impairment as a consequence of unhealthy lifestyle, notably with the increased risk of cardiovascular risk factors that inflate the morbidity in this category of patients [30] , [43] , [44] , [45] , [46] , [47] .…”
Section: Discussionmentioning
confidence: 99%
“…With respect to the analysis of food waste in respondents' consumption, it is somehow normal that the amount of waste should increase during the pandemic period, once food consumption was mainly done at home through cooked food (Jribi et al, 2020). In the literature, it is well known that, during the pandemic, the consumption of cooked food increased (Borsellino et al, 2020;Wachyuni and Wiweka, 2020;Bakhsh et al, 2021;Gerritsen et al, 2021;Jaeger et al, 2021;Koletzko et al, 2021) and, along with it, the amount of waste (at least in the first part of the pandemic-the beginning of the year 2020) (Aldaco et al, 2020;Jribi et al, 2020). During this period, some consumers seem to attain a much better equilibrium in terms of food waste (Pappalardo et al, 2020;Iranmanesh et al, 2022), while others still do not even consider food waste a real problem in terms of economics, social, and environmental impacts (Pocol et al, 2020).…”
Section: Shopping Patternsmentioning
confidence: 99%